2022 IEEE 47th Conference on Local Computer Networks (LCN) 2022
DOI: 10.1109/lcn53696.2022.9843413
|View full text |Cite
|
Sign up to set email alerts
|

A Live Demonstration of In-Band Telemetry in OSM-Orchestrated Core Networks

Abstract: Network Function Virtualization is a key enabler to building future mobile networks in a flexible and cost-efficient way. Such a network is expected to manage and maintain itself with minimum human intervention. With early deployments of the fifth generation of mobile technologies -5G -around the world, setting up 4G/5G experimental infrastructure is necessary to optimally design Self-Organising Networks (SON). In this demo, we present a custom small-scale 4G/5G testbed. As a step towards self-healing, the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Dreibholz et al [ 93 ] describe a 4G/5G testbed where P4 switches are used to perform in-band network telemetry. The telemetry data is sent to a collector that gathers information about traffic flows and switch queue status.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dreibholz et al [ 93 ] describe a 4G/5G testbed where P4 switches are used to perform in-band network telemetry. The telemetry data is sent to a collector that gathers information about traffic flows and switch queue status.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The study described in [ 93 ] demonstrates that the end-to-end round trip time (RTT) and dequeue time can be accurately measured using their implementation of INT. Another work in [ 94 ] reported that the INT load did not have a significant impact on end-to-end latency, as it was found to be below 1 ms.…”
Section: Findings and Discussionmentioning
confidence: 99%